Against popery : Britain, empire, and Anti-Catholicism - Haefeli, Evan, 1969- (Early American histories., 2020)
"Against Popery: Britain, Empire, and Anti-Catholicism is a collection of interdisciplinary essays that use anti-popery as a framework for interpreting the culture and politics of the British-American world. Anti-popery is identified by scholars of early modern England as an ideology of liberty associated with anti-Catholicism-an opposition to tyranny and corruption associated with the papacy. Spanning three centuries, these essays reveal anti-popery as an agent of cultural and political change, from Protestants' positive engagement with selected aspects of Catholic culture to upheavals like the American Revolution"--